(untitled) (VITEK : Bidang Kedokteran Hewan, 2024)
Scabies is a common skin disease in cats caused by mite infestation, one of which is Sarcoptes scabiei. An unsterilized male domestic 4 years old cat, weighing 4.75 kg, with a history of hair loss and itching. On physical examination, lesions were found in the form of alopecia, papules, hyperkeratosis, erythema, crusting, scales, escoriation and ulcers on the skin of the cat’s face, ears and neck. The mucosa of the cat’s mouth and eyes is pale and swelling of the lymphnodes with a hard consistency and increased temperature of the overlying skin. Laboratory examinations showed the presence of Sarcoptes scabiei mites accompanied by normocytic-normochromic anemia and abnormalities in the cat’s hair medulla. Treatment given includes administration of ivermectin (0.2 mg/kg BW subcutaneously), chlorphenamine maleate (2 mg/head orally once a day), gentamicin sulfate ointment, multivitamins and minerals 1 tab/head orally once a day), administration of one softgel of fish oil per day, application of Virgin Coconut Oil, and specific food for hair and skin (Royal Canin®). On the seventh day, the case cat showed clinical recovery with relief of disease symptoms such as itching and reduction of lesions.